Urgensi Berpikir Kritis dalam Pemanfaatan Media Sosial untuk Katekese Digital - Karolus Teguh Santoso; Emmeria Tarihoran (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
This article discusses the urgency of critical thinking skills in utilizing social media as a means of digital catechesis. Amidst the rapid and diverse flow of information in the digital era, critical thinking becomes an essential skill to avoid the spread of inaccurate or misleading information, especially in the context of conveying the teachings of faith. Social media does offer great potential as a medium for evangelization and catechesis, but the main challenge is the validity of the content which is often not verified. Therefore, digital catechesis teachers and participants are required to be able to analyze, evaluate, and filter information selectively and objectively. This article also outlines strategies for developing critical thinking skills, such as media literacy training, guided discussions, and the use of interactive content. By strengthening critical thinking skills, digital catechesis is expected to become an educational and transformative means in conveying faith values ​​relevantly and responsibly in the digital space.